PENGARUH IMPLEMENTASI KEBIJAKAN TERHADAP EFEKTIVITAS PEMBANGUNAN INFRASTRUKTUR DI DESA PANYADAP KECAMATAN SOLOKANJERUK KABUPATEN BANDUNG - Aisyah, Pratiwi; Indah, Diani (Jurnal Sosial Politik Unla, 2023)
The problem in this research is the ineffectiveness of infrastructure development in Panyadap Village, Solokanjeruk District, Bandung Regency. Based on these problems, the researcher formulated the problem as follows: How Big is the Influence of the Implementation of Panyadap Village Government Policies on the Effectiveness of Infrastructure Development in Panyadap Village, Solokanjeruk District, Bandung Regency. In analyzing the problems studied, the authors propose the theory of policy implementation from George C Edwards III (in Subarsono 2011: 90- 92) with the dimensions of Communication, Resources, Disposition/Attitude and Bureaucratic Structure. While the theory of effectiveness from Duncan in Steers (2008:53) with dimensions namely Goal Achievement, Integration, and Adaptation. Based on this framework, the hypothesis formulated is: "The magnitude of the influence of policy implementation on the effectiveness of infrastructure development in Panyadap Village, Solokanjeruk District, Bandung Regency, is determined by the implementation of the dimensions of Communication, Resources, Disposition/Attitude and Bureaucratic Structure". The research method used is an explanatory method with a quantitative approach. The results of testing the formulated hypothesis show that the policy implementation variable has a moderate and significant relationship between Policy Implementation and Infrastructure Development Effectiveness. In addition, another variable was found that also influenced the effectiveness of infrastructure development, namely the monitoring variable. This the results of this study tested empirically.